Предмет: Математика,
автор: nikpostolaku
Упростить выражение 3×(12-2×27)
Ответы
Автор ответа:
0
√3(√12-2√27)=√36-√3(2√27)=6-2√81=6-2*9=6-18=-12
вроде так
вроде так
Автор ответа:
0
Благодарю
Автор ответа:
0
А почему так
Автор ответа:
0
Ну я со своей тетрадки писала, но я точно 100% не уверена что правильно, я точно не помню, извини если не правильно
Похожие вопросы
Предмет: Химия,
автор: Anastasiagrishuk3
Предмет: Математика,
автор: miruwq
Предмет: Математика,
автор: Realme157000
Предмет: Математика,
автор: nikita552004